Enhanced dynamic scheduling for uplink latency reduction in broadband volte systems - MAŞAZADE, ENGİN (My University, 2022)
Uplink (UL) scheduling is very important for the efficient use of VoLTE. Dynamic Scheduling (DS) and Semi-Persistent Scheduling (SPS) are two main methods used for UL scheduling. In DS, before each transmission, the user equipment (UE) sends a Scheduling Request (SR) and the eNodeB (eNB) sends back an UL grant to the UE involving the Modulation and Coding Scheme (MCS) for that transmission. Therefore, DS can respond to rapidly changing channel conditions quickly, but involves a control signaling overhead. In SPS, the eNB assigns resources to the UE without waiting for a SR from the UE. Hence, SPS reduces the control signaling overhead, but since the MCS is defined at the beginning of the transmission, SPS becomes less responsive to changing channel conditions. To solve the adaptation problem without compromising on low latency, we propose a new scheduling method, Enhanced Dynamic Scheduling (EDS). Since the packet time interval of voice packets is constant, EDS grants resources to UEs periodically and dynamically based on their needs. Test results show that proposed method is adaptive to changing channel conditions and decreases the latency as compared to DS and SPS under both ideal and realistic channel conditions.
Keywords: Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Haberleşme Mühendisliği; Mühendislik ve Teknoloji; Information Systems, Communication and Control Engineering; Communication Engineering; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; TELEKOMÜNİKASYON; Engineering, Computing & Technology (ENG); ENGINEERING; TELECOMMUNICATIONS; Computer Networks and Communications; Physical Sciences